Implementasi Metode Profile Matching Pada Sistem Pendukung Keputusan Pemilihan Penerima Bantuan Langsung Tunai di Desa Pondo Kecamatan Lembor - Emiliana Indra Rati; Rini Agustina (LPPM UBHINUS MALANG, 2022)
The direct cash assistance program (DCA) by the government is intended to provide concrete efforts to recover the economy of the underprivileged. In fact, several technical problems in the field led to confusion in the determination of BLT targets. In Pondo village, there was an inaccurate targeting process due to: (1) kinship ties between village officials and the community; (2) does not have a clear standard of criteria to determine beneficiaries. This study aims to encourage efforts to build a decision support system that can solve current problems by implementing the profile matching method to determine recipients of direct cash assistance based on ranking so that data accuracy for DCA Program recipients occurs. The research method used is the waterfall method, data analysis uses the calculation steps of the profile matching method. The results showed that the system that was built had helped the process of calculating the assessment for the selection of DCA Program recipients with an average UAT of 99.5%. This shows that the profile matching method used is in accordance with the design that has been made. It can be concluded that the use of profile matching method is very effective in determining the target of DCA Program recipients. This research can be a reference for the village government to use the decision support system that has been built so that the main target of the DCA Program is in accordance with the provisions that have been set.